Wages and Establishment Size - Swimmer, David (Relations industrielles / Industrial Relations, 1978)
The author examines some of the more prominent research in the light of their author symethodologies and then, using current wage-size data, illustrates that size, per se, is not a determinant of wages; other factors interacting with size can produce higher wages, but do not necessarily have to do so.